IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR DI KANTOR SATUAN KERJA PERENCANAAN DAN PENGAWASAN JALAN NASIONAL PROVINSI BENGKULU (Studi Pada Bidang Bendahara Pengeluaran Pembantu Pejabat Pembuat Komitmen Pengawasan) - Puspita, Tiara Puspita (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research aims to determine the implementation of standard operational procedures for the financial administration of the treasurer's expenditure on assistant officials who make supervisory commitments. The data analysis method used is qualitative analysis. The results of the research show that: (1) Implementation of Standard Operational Procedures at the Bengkulu Province National Road Planning and Supervision Work Unit Office in the Treasurer Sector, Expenditures of Assistant Commitment Making Officials, the implementation has gone well in accordance with standard operational procedures set by the Ministry of PUPR. Implementation of standard operational procedures is also followed properly by the project consultant (2) If the files or billing documents from the project consultant are incomplete, they will be returned to the project consultant so that the files are complete in accordance with standard operational procedures (3) The Commitment Making Officer Supervision assigns tasks and the responsibility of the project consultant to supervise project control in terms of quality, quantity and costs (4) If the billing files or documents are incomplete. The Official Signing the Payment Order cannot disburse or process it.Â Keywords : Implementation, standard operating procedures, financial administration